Zulkifli Mohd Yusoff & Zaini Ujang (2023), Tafsir Mawdu’i Sungai, Kajang: Akademi Jawi Malaysia. 251 Pages, ISBN 978-967-2422-50-1 Article Sidebar - Norhasnira Ibrahim (Centre of Quranic Research (CQR), University of Malaya, 2026)
Tier 2 (Index by SCOPUS)